Vmp1, Vps13D, and Marf/Mfn2 function in a conserved pathway to regulate mitochondria and ER contact in development and disease - Shen, James L.; Fortier, Tina M.; Zhao, Yan G.; Wang, Ruoxi; Burmeister, Margit; Baehrecke, Eric H. (Current biology, 2021)
Mutations in Vps13D cause defects in autophagy, clearance of mitochondria, and human movement disorders. Here, we discover that Vps13D functions in a pathway downstream of Vmp1 and upstream of Marf/Mfn2. Like vps13d, vmp1 mutant cells exhibit defects in autophagy, mitochondrial size, and clearance. Through the relationship between vmp1 and vps13d, we reveal a novel role for Vps13D in the regulation of mitochondria and endoplasmic reticulum (ER) contact. Significantly, the function of Vps13D in mitochondria and ER contact is conserved between fly and human cells, including fibroblasts derived from patients suffering from VPS13D mutation-associated neurological symptoms. vps13d mutants have increased levels of Marf/MFN2, a regulator of mitochondrial fusion. Importantly, loss of marf/MFN2 suppresses vps13d mutant phenotypes, including mitochondria and ER contact. These findings indicate that Vps13d functions at a regulatory point between mitochondria and ER contact, mitochondrial fusion and autophagy, and help to explain how Vps13D contributes to disease. [Display omitted] •Vps13D and Vmp1 are linked as regulators of autophagy and mitochondrial morphology•Vps13D, like Vmp1, regulates mitochondria and ER contact sites•Vps13D regulates mitophagy and mitochondrial morphology downstream of Vmp1•Vps13D mitochondria and ER contact phenotypes depend on Marf/MFN2 The clearance of mitochondria by mitophagy is important for cell health. Shen et al. identify Vps13D as functioning in a pathway with Vmp1 and Marf/Mfn2 to regulate mitophagy. Loss of Vps13D in flies and cells derived from patients with movement disorders also impacts mitochondria and ER contact, and these cellular defects depend on Marf/MFN2.